Small Cell Ovarian Cancer in Adolescents: Report of Two Cases and Review of the Literature - M. Rovithi; A. G. Pallis; A. Kalykaki; E. Lagoudaki; L. Giannikaki; E. N. Stathopoulos; K. Relakis; V. Georgoulias (Case Reports in Medicine)
Ovarian small cell carcinoma is a rare and highly malignant neoplasm carrying a poor prognosis. Although combination chemotherapy remains the cornerstone of treatment due to the rarity of these tumors, no regimen can be recommended as standard of care although in the majority of cases platinum-based regimens are used. Herein, we report two cases of small cell carcinoma of the ovaries along with a review of the relevant literature.